The use of the storytelling method to improve the speaking skills of grade 9 students - Azizati Nur Firdaus; Pariyanto Pariyanto (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
The ability to speak is one of the English language skills that must be mastered to facilitate learning. This research was motivated by the formulation of problems that occurred in the Nafi Mumtaza learning house institution which had 4 students. This study aims to improve students' speaking skills and confidence levels when speaking in English. Although the research objects are few, researchers try to use learning alternatives that are easy to apply and strongly support this research. Therefore, the researcher decided to use the storytelling method. This study used the type of Classroom Action Research (PTK) using Kemmis and Mc Taggart spiral model design learning guidelines. Learning improvement is carried out in 2 cycles and assessment is seen from the aspect of students' understanding of the story presented and the ability to convey it back in front of the class. In the cycle 1 stage, only 25%, namely 1 student, are able to achieve the minimum score of 75 and this increases in the cycle 2 stage to 50%, namely 87 and 89 if assessed with 3 categories, and reaches 100% complete achievement, namely 91 and 94 if using pure value acquisition, a comparison with absorption and ideal values. These results prove that the speaking ability of students in English learning has improved with the application of storytelling learning methods